Significance of the natural convection to the heat transfer of porous media: a pore-scale study - Xuan, Zi-Hao (2024)
Heat conduction in porous media is generally accompanied by the natural convection of the fluid within the pores driven by the temperature gradient. However, the criterion to determine the critical pore size of porous media where the natural convection cannot be neglected remains elusive. In this study, a pore-scale model is established to investigate the contributions of natural convection on the effective thermal conductivity (ETC) of porous media, which takes the reconstructed microstructures as the geometry input. We thus examine the effects of the porosity, thermal conductivity of the fluid and solid phases, and heating direction on the critical pore size where the natural convection starts to work. The results show that the critical pore size decreases with increasing porosity and heating temperature, but increases with the rise in the thermal conductivity of solid phase. Moreover, the critical pore size is significantly lower for the lateral heating, compared with the bottom heating. Finally, we proposed a new formula as an indicator to determine the significance of natural convection to the heat transfer in porous media.